2019
DOI: 10.1136/flgastro-2019-101199
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement initiative increases total paracentesis and early paracentesis rates in hospitalised cirrhotics with ascites

Abstract: ObjectiveEarly paracentesis (EP) for rapid diagnosis of spontaneous bacterial peritonitis is considered best practice in the care of admitted patients with cirrhosis and ascites, but inpatient paracentesis is frequently not performed or delayed. We developed a quality improvement (QI) initiative aimed at increasing the proportion of admitted patients with cirrhosis who undergo paracentesis and EP.Design Pre–post study of a QI initiative.Setting A tertiary care hospital in a major metropolitan area.Patients Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Such outcomes may significantly reduce early bedside paracentesis performed by ED physicians. This is further supported by a recent quality improvement project where a gap analysis performed to identify barriers to paracentesis reported that time and personnel required in the ED were the most common reasons cited [ 20 ].…”
Section: Discussionmentioning
confidence: 81%
“…Such outcomes may significantly reduce early bedside paracentesis performed by ED physicians. This is further supported by a recent quality improvement project where a gap analysis performed to identify barriers to paracentesis reported that time and personnel required in the ED were the most common reasons cited [ 20 ].…”
Section: Discussionmentioning
confidence: 81%
“…Routine correction of international normalized ratio (INR) and/or platelets is not required before diagnostic paracentesis, and the risk of bleeding is low even in patients with INR > 1.5 and platelets < 50 × 10 9 /L 5,6,11 . Given that diagnostic paracentesis is an essential early intervention in patients with cirrhosis with ascites, which informs additional downstream, time-sensitive critical interventions, it is important to emphasize the importance of this procedure in EM practice 15 …”
Section: Infection/spontaneous Bacterial Peritonitismentioning
confidence: 99%
“…[5,6,11] Given that diagnostic paracentesis is an essential early intervention in patients with cirrhosis with ascites, which informs additional downstream, time-sensitive critical interventions, it is important to emphasize the importance of this procedure in EM practice. [15] Intervention: Antibiotics When suspicion of infection/sepsis is high, empiric antibiotics should be initiated immediately after cultures have been collected. [5] For SBP, once diagnosed by ascites neutrophil count, antibiotics should not be delayed while awaiting culture data.…”
Section: Intervention: Diagnostic Paracentesismentioning
confidence: 99%
“…Indeed, Jesudian et al proved that a quality-improvement initiative based on increasing the awareness of emergency medicine and internal medicine specialists, as well as providing procedural training, increased the rate of patients receiving a paracentesis within 12 hours from admission, from 48% to 81% in pre-intervention and post-intervention phases, respectively. [9] Another potential barrier to the implementation of paracentesis concerns the low reimbursement rate for the procedure. In fact, the high value of paracentesis is poorly recognized by the current reimbursement rate.…”
mentioning
confidence: 99%
“…Diagnostic paracentesis is a procedure that requires simple equipment and takes only a few minutes to be performed properly; therefore, the implementation of early paracentesis mainly concerns the training of physicians and awareness of its value for patient care. Indeed, Jesudian et al proved that a quality-improvement initiative based on increasing the awareness of emergency medicine and internal medicine specialists, as well as providing procedural training, increased the rate of patients receiving a paracentesis within 12 hours from admission, from 48% to 81% in pre-intervention and post-intervention phases, respectively 9 . Another potential barrier to the implementation of paracentesis concerns the low reimbursement rate for the procedure.…”
mentioning
confidence: 99%